ParentCoach: designing an mHealth parenting app to enhance parental involvement in ADHD support - Cibrian, Franceli L.; Herrera, Nancy; Beltran, Jesus A.; Silva, Lucas M.; Pulse, Mikaela; Anderson, Kayla; Zeiler, Cassie; Arnold, Vitica X.; Rieffel, Luc; Lee, Daniel I.; Schuck, Sabrina E. B.; Lakes, Kimberley D. (Frontiers in Computer Science, 2025)
IntroductionParents play a vital role in supporting self-regulation and managing behaviors in children with Attention-Deficit/Hyperactivity Disorder (ADHD). However, many face barriers to accessing consistent, evidence-based support. Mobile health (mHealth) technologies offer a promising way to deliver flexible, low-burden guidance for parents on best practices and strategies to support their children's self-regulation. However, designing them is non-trivial.ObjectiveThis paper introduces ParentCoach, a mobile application designed to support parents of children with ADHD through brief daily lessons, reflection prompts, and skill-building activities.MethodsParentCoach was developed in two phases: (1) secondary analysis of qualitative data from over 30 families using mHealth tools to support self-regulation, and (2) co-design with ADHD experts to refine and validate the curriculum.ResultsOur findings identify key design needs for digital parenting tools: micro-interactions, flexible content formats, scaffolding for executive function, and emotional reflection. The resulting app delivers an 80-lesson curriculum across 16 weekly themes covering relational self-reflection, emotional regulation, communication, and behavior management.DiscussionParentCoach design and development show how evidence-based parenting strategies can be translated into accessible, scalable mHealth interventions. Our study offers key design implications for digital tools that support parent learning, emotional resilience, and behavioral consistency in the home. Currently, we are running a randomized controlled trial to provide evidence of ParentCoach's impact. This work contributes to ongoing efforts to develop technology-enhanced behavioral interventions for families of children with ADHD.